Circulation levels of acute phase proteins pentraxin 3 and serum amyloid A in atherosclerosis have correlations with periodontal inflamed surface area - Başak Temelli; Zuhal Yetkin Ay; Hasan Basri Savaş; Fatih Aksoy; Duygu Kumbul Doğuç; Ersin Uskun; Ercan Varol (University of São Paulo, 2018)
Abstract Objectives One of the plausible mechanisms in the relationship between periodontitis and coronary artery disease (CAD) is the systemic inflammatory burden comprised of circulating cytokines/mediators related to periodontitis. This study aims to test the hypothesis that periodontal inflamed surface area (PISA) is correlated with higher circulating levels of acute phase reactants (APR) and pro-inflammatory cytokines/mediators and lower anti-inflammatory cytokines/mediators in CAD patients. Material and Methods Patients aged from 30 to 75 years who underwent coronary angiography with CAD suspicion were included. Clinical periodontal parameters (probing depth - PD, clinical attachment loss, and bleeding on probing - BOP) were previously recorded and participants were divided into four groups after coronary angiography: Group 1: CAD (+) with periodontitis (n=20); Group 2: CAD (+) without periodontitis (n=20); Group 3: CAD (-) with periodontitis (n=21); Group 4: CAD (-) without periodontitis (n = 16). Serum interleukin (IL) −1, −6, −10, tumor necrosis factor (TNF)-α, serum amyloid A (SAA), pentraxin (PTX) 3, and high-sensitivity C-reactive protein (hs-CRP) levels were measured with ELISA. Results Groups 1 and 3 showed periodontal parameter values higher than Groups 2 and 4 (p<0.0125). None of the investigated serum parameters were statistically significantly different between the study groups (p>0.0125). In CAD (-) groups (Groups 3 and 4), PISA has shown positive correlations with PTX3 and SAA (p<0.05). Age was found to predict CAD significantly according to the results of the multivariate regression analysis (Odds Ratio: 1.17; 95% Confidence Interval: 1.08-1.27; p<0.001). Conclusions Although age was found to predict CAD significantly, the positive correlations between PISA and APR in CAD (-) groups deserve further attention, which might depend on the higher PISA values of periodontitis patients. In further studies conducted in a larger population, the stratification of age groups would provide us more accurate results.